A behavioral perspective on visualization in manufacturing and operations management: a review, framework, and research agenda - Fabian Lindner; Gerald Reiner; Sophia Keil (Operations Management Research, 2025)
Visualizations are ubiquitous in today's manufacturing operations, whether in the form of time series, scatter plots, flow charts, or dashboards. Managers, engineers, and shop-floor workers use visualizations to understand and act on production data for monitoring, problem solving, decision making, and strategy development. How we present the information we need influences our actions and behaviors. Therefore, we systematically review and analyze the current literature in manufacturing and operations management on visualizations and their relationship to behavioral operations in terms of social, cognitive, and emotional benefits as well as resulting performance improvements of production systems. Through content analysis of 64 papers from 1997 to 2023 across eight operational contexts and types of visualizations, we find typical purposes, benefits, and pitfalls where behavioral mechanisms are prevalent. Visualizations are used to facilitate knowledge explanation and sharing for improved communication and collaboration, or to reduce cognitive load and mental cost for increased quality and resource efficiency in task execution. The results are synthesized in an integrative framework that explains the links between visualizations and operations through their common behavioral mechanisms. We propose eight directions and map concrete hypotheses for future research in this area to promote the targeted development, deployment, and evaluation of visualizations in manufacturing considering behavioral and operational performance factors. Our study contributes to the emerging literature on visualizations in operations management, provides an overview and guidance for further efforts in this area, and helps practitioners reflect on and improve their design and use of visualizations, thereby advancing their management toolbox.
Keywords: 510; Information and data visualization; Manufacturing; Behavioral operations management; Systematic literature review; Content analysis